Facilitation of Enrollment onto Cancer Clinical Trials Using a Novel Navigator-Assisted Program: A Cross-Sectional Study - Mahmoud Hossami; Rhonda Abdel-Nabi; Farwa Zaib; Kayla Touma; Renee Nassar; Sanghyuk Claire Rim; Milica Paunic; Olla Hilal; Pratham Gupta; Roaa Hirmiz; Michael Touma; Govana Sadik; et al. (Current Oncology)
Introduction: Clinical trials are essential to the advancement of clinical therapies that improve the outcomes of people with cancer. However, enrollment in clinical trials remains a challenge. The Clinical Trial Navigator [CTN] Program was designed to address the current gap in the cancer care journey by assisting with the clinical trials search process. Methods: Between March 2019 and July 2024, applicants of the CTN program included people with cancer, their family members, and/or their care team. Applicants entered the CTN program through a REDCap® survey that collected the patient’s medical history. A final curated list of potential clinical trials was provided to the applicant. Metrics of success included clinical trial referral and enrollment, and we examined the factors that impacted these outcomes. Results: A total of 445 people with cancer applied to the CTN program during the study. Of the 262 patients with referral and enrollment information, a trial referral occurred in 27.5% [n = 72]. Of the 72 patients who were referred to a clinical trial, 13 [18.1%] were enrolled, 9 [12.5%] are pending enrollment, and 50 [69.4%] were not enrolled. We identified a potential trial for 88% of applicants, with a median of one potential trial per patient. Physicians were highly involved as applicants. Interpretation: The CTN program is successful in searching for clinical trials for people with cancer. Ongoing implementation into other Canadian sites, assessments of patient-reported outcomes, website and social media campaigns, and research into the factors that impact referral and enrollment are underway.